Preponderance of blaKPC-Carrying Carbapenem-Resistant Enterobacterales Among Fecal Isolates From Community Food Handlers in Kuwait - Moghnia, Ola H.; Rotimi, Vincent O.; Al-Sweih, Noura A. (Frontiers in Microbiology, 2021)
Carbapenem-resistant Enterobacterales (CRE) are pathogens that have been found in several countries with a significant public health concern. Characterizing the mode of resistance and determining the prevailing clones is vital to the epidemiology of CRE in our community. This study was conducted to characterize the molecular mode of resistance and determine the clonality of the CRE fecal isolates among community food handlers (FHs) versus infected control patients (ICPs) in Kuwait. Fecal CRE isolates obtained from FHs and ICPs during September 2016 - June 2018 were analyzed for their resistance genes. Genes characterization was carried out by polymerase chain reaction (PCR) assays and sequencing. Clonality of isolates was established by multilocus sequence typing (MLST). Of the 681 and 95 species of the family Enterobacterales isolated from FHs and ICPs, 425 (62.4%) and 16 (16.8%) were Escherichia coli and 18 (2.6%) and 69 (72.6%) were Klebsiella pneumoniae, respectively. A total of 36 isolates were CRE with a prevalence of 5.3% among FH isolates and 87 (91.6%) among the ICPs. Of these, carbapenemase genes were detected in 22 (61.1%) and 65 (74.7%) isolates, respectively (P <0.05). The detected specific genes among FHs and ICPs were positive for: blaKPC 19 (86.4%) and 35 (40.2%), blaOXA 10 (45.5%) and 59 (67.8%), in addition to blaNDM 2 (9.1%) and 32 (36.8%), respectively. MLST typing assays of the E. coli and K. pneumoniae isolates revealed considerable genetic diversity and polyclonality as well as demonstrated multiple known ST types and 8 novel sequence types. The study revealed a relatively high number of CRE harboring predominantly blaKPC mediated CRE among the community FH isolates versus predominant blaOXA genes among the ICPs. Those heterogeneous CRE isolates raise concerns and mandate more efforts towards molecular surveillance. A multi-national study is recommended to monitor the spread of genes mediating CRE in the community of Arabian Peninsula countries.